Micro-CT analysis of cracked tooth in the second mandibular molar with C anatomy after occlusal trauma: Case report (Research, Society and Development, 2021)
The aim of the present study was to analyze in a micro-CT tooth extracted by cracked. A 38-year-old white woman, complaining of occasional discomfort when biting popcorn kernels, sought emergency care. After intraoral and radiographic clinical examination, the right second mandibular molar (tooth 47) was diagnosed with live pulp and fracture of the lingual cusps, and after removal of the amalgam restoration, an incomplete fracture initiated from the crown was found in the distal proximal crest. The treatment plan started with prosthetic rehabilitation using a full crown. Three months later symptomatic irreversible pulpitis was diagnosed. The pulp cavity was accessed through the prosthetic crown and the tooth was treated endodontically. Two years later, the patient presented a fistula close to the gingival sulcus and a 12mm periodontal probe in the center of the distal surface. Cone-beam tomographic examination reveals extensive bone loss reaching the mandibular canal. The treatment plan was extraction of the dental elemento and subsequent implant planning. The extracted tooth was then subjected to scanning at the micro-CT. In the analysis of the micro-CT images of the extracted tooth, it was found cracked tooth, extending from the crown to the proximal root (distal face). There was also a bad adaptation of the gutta-percha cone in the apical third of the endodontic treatment performed. Through this report, we can infer that the diagnosis of cracked tooth is a challenge in clinical practice, and the corono-radicular spread of crack is associated with microbial infiltration and consequent risk of loss of the dental element.